Pengembangan Computer Based Testing (CBT) pada Pembelajaran Teknologi Informasi dan Komunikasi untuk kelas VIII SMP - Syahril Akmal; Syafril Syafril; Nofri Hendri (Universitas Negeri Padang, 2022)
The background of this research is because of processing in evaluation at Junior High School 16 Padang which still used the old method or conventional. This evaluation is still have problem to determine the students ability directly in other word, this method needed the long time for getting students’ score. It this because of teacher must search students’ score manually. Based on the problem above appears the purpouse of this research is to make Computer Based Testing (CBT) product in TI&K Teaching Learning process at eighth grade of Junior High School. This research used Research and Development (R & D) method. Which concist in 10 Steps. Although, these steps is more minimilize to be 5 (five) steps, such as; (a) planning, (b) developing the first product, (c) validation (material and product), (d) hypoteses for determining of practical CBT, and (e) the last result of product, is created a tool to evaluate in learning process. Based on the result of data analysis pointed that CBT product is can be categoriezed to use. To result of part all answers can be categorized to use. And to the practical CBT also can be categorized is good or can be used in learning. From the result of this research can be concluded that CBT product is can be used as a tool in evaluation on learning process.